In Silico Study of Genus Marchantia using matK loci for DNA Barcoding - Farhan, Abdillah Maulana; Ulum, Fuad Bahrul (Department of Biology, Faculty Mahematics and Natural Sciences, University of Jember, 2024)
Marchantia is a genus of liverworts that can be found in the Asia-Europe Region. Some of the types that can be found are Marchantia polymorpha subsp. montivagans, Marchantia polymorpha subsp. ruderalis, Marchantia paleacea subsp. diptera. All of these species have different levels of kinship, this is due to differences in their nucleotide structure. The purpose of this study was to identify the intolerance between Marchantia species in genomic studies using the NCBI Database. The method used in this research is the collection of nucleotides on NCBI and then construction with Mega 11 software. The marker used in this study is Maturase K (matK), this is because the marker is very optimal in the identification of a molecular-based species. The results of this study are Marchantia paleacea subsp. diptera matK (MP 58 and MP 54) has the highest level of kinship with a score of 99 (Neighbor-Joining Tree) and 100 (Maximum Likelihood Tree) and the outgroup of this phylogenetic is Dumortiera hirsuta. Keywords: Marchantia, matK, NCBI, Phylogenetic.